Correlation between adult mosquito density and meteorological factors in Pudong New Area of Shanghai, China - GE Ge; YUAN Yongting; FENG Lei; LIU Hanzhao; LIN Chen; GU Ruohua; GE Juan; LIU Jun (Shanghai yufang yixue)
ObjectiveTo learn the density and seasonal variation of adult mosquitoes in Pudong New Area of Shanghai, and to explore the influence of meteorological factors on the density of adult mosquitoes.MethodsFrom April to November in 2017‒2021, adult mosquito density in Pudong New Area was monitored every ten days a time by using CO2 trapping light method. Meteorological data were collected during the same time, and Pearson correlation analysis and multiple linear regression model were used to investigate the correlation between adult mosquito density and meteorological factors.ResultsThe seasonal variation of adult mosquito density showed a single-peak pattern, with the peak of 7.09 mosquitoes·(set·time)-1 in July. The adult mosquito density was positively correlated with the monthly average temperature, monthly maximum temperature, monthly minimum temperature, and monthly average relative humidity (r=0.813, 0.793, 0.820, 0.617, all P<0.05), but negatively correlated with monthly average air pressure (r=-0.738, P<0.05). The regression equation of the adult mosquito density and monthly minimum temperature in Pudong New Area of Shanghai was Y=0.066 X3-0.884, with a corrected R2 of 0.673, indicating a good model fitting.ConclusionThe overall seasonal variation of adult mosquito density in Pudong New Area showed a single-peak pattern. The density of adult mosquitoes was correlated with the monthly average temperature, monthly maximum temperature, monthly minimum temperature, monthly average relative humidity, and monthly average air pressure, and linearly correlated with monthly minimum temperature.